اتجاهات المعلمين نحو استخدام مبادئ نظرية التعلم المستند إلى الدماغ: دراسة ميدانية على عينة من معلمي الحلقة الأولى في مدينة اللاذقية - حمادة، وليد; خليفة، أحمد حسن; إسكندر، حسين عزيز (جامعة تشرين, 2024)
هدف البحث الحالي إلى تعرف اتجاهات معلمي الحلقة الأولى من التعليم الأساسي في مدارس مدينة اللاذقية نحو استخدام مبادئ التعلم المستند إلى الدماغ، وعلاقة هذا الاتجاهات بمتغيري المؤهل العلمي للمعلم وعدد سنوات خبرته. استخدم المنهج الوصفي، وكانت أداة البحث استبانة معدة من قبل الباحث، وشملت عينة البحث (280) معلم ومعلمة من معلمي الحلقة الأولى للتعليم الأساسي في مدارس مدينة اللاذقية. أظهرت نتائج البحث أن أفراد عينة البحث يمتلكون اتجاهات محايدة نحو استخدام مبادئ نظرية التعلم المستند إلى الدماغ. وأن عدد سنوات خبرة المعلم/ المعلمة يؤثر في اتجاهاتهم نحو استخدام مبادئ نظرية التعلم المستند إلى الدماغ لصالح المعلمين ذوي عدد سنوات الخبرة الأكبر. إلا أن المؤهل العلمي للمعلم/ المعلمة لم يؤثر في اتجاهاتهم نحو استخدام مبادئ نظرية التعلم المستند إلى الدماغ. The current research aims to explore the attitudes of primary school teachers in Latakia city towards the use of brain-based learning principles, and the relationship of these attitudes with the teachers' academic qualifications and years of experience. The study utilized a descriptive methodology, with a questionnaire developed by the researcher as the research tool, and included a sample of (280) male and female teachers from the first cycle of basic education in the schools of Latakia. The research results indicate that the individuals in the sample possess neutral attitudes towards the use of brain-based learning principles. Additionally, the number of years of experience of the teacher influences their attitudes towards the use of brain-based learning principles in favor of teachers with more experience. However, the academic qualifications of the teacher did not affect their attitudes towards the use of brain based learning principles.
Keywords: استراتيجيات التعليم -- التعلم المستند إلى الدماغ -- مرحلة التعليم الأساسي